1986
DOI: 10.1111/j.1745-4514.1986.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Tmao Degrading Systems in Atlantic Short Finned Squid (Illex Illecebrosus)

Abstract: The decomposition of trimethylamine oxide (TMAO) to dimethylamine (DMA) was studied in the mantle of squid, Illex illecebrosus. The production of DMA in either whole or ground mantle stored at – 20°C was low or nonexistent. However, significant DMA was produced from TMAO during heating of squid or squid extracts. Conversion of TMAO to DMA was shown to reside in the soluble fraction of the squid mantle which catalyzed the breakdown of TMAO in an assay system consisting of FeCl2 and ascorbate at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A recent study similarly described that the non‐enzymatic decomposition of TMAO was crucial during thermal processing of squid 13. A significant amount of DMA was produced from TMAO during heating of Atlantic short finned squid or squid extract, whereas the formation of DMA in either whole or ground mantle stored at − 20 °C was low or non‐existent 10. Lin and Hurng14 reported that the level of production of TMA and DMA from TMAO by non‐enzymatic pathways depended on the heating temperature in dried squid.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study similarly described that the non‐enzymatic decomposition of TMAO was crucial during thermal processing of squid 13. A significant amount of DMA was produced from TMAO during heating of Atlantic short finned squid or squid extract, whereas the formation of DMA in either whole or ground mantle stored at − 20 °C was low or non‐existent 10. Lin and Hurng14 reported that the level of production of TMA and DMA from TMAO by non‐enzymatic pathways depended on the heating temperature in dried squid.…”
Section: Resultsmentioning
confidence: 98%
“…The enzymatic decomposition of TMAO in gadoid fish such as cod and hake during frozen storage is a main source of FA and DMA formation. Endogenous TMAOase isolated from the mantle of squid induces the breakdown of TMAO to DMA and FA 10, 11. Besides the enzymatic pathway of FA production, FA, DMA and trimethylamine (TMA) are steadily accumulated during the processing of squid, thus affecting their physicochemical properties 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Two main possible pathways for the degradation of TMAO have been proposed. One is that the enzymatic reaction produces equimolar DMA and FA from TMAO, which is catalysed by trimethylamine-N-oxide demethylase (TMAOase) (Fu et al, 2008;Leelapongwattana, Benjakul, Visessanguan, & Howell, 2008b;Nitisewojo & Hultin, 1986;Stanley & Hultin, 1984). The other suggested pathway is a microbial spoilage reaction, resulting in redox-potential decrease, pH increase, and electrical conductance increase, in which TMAO degrades to trimethylamine (TMA) (Ayensa & Gomez-Guillen, 1999;Fu et al, 2008;Krzymien & Elias, 1990;Lundstrom & Racicot, 1983;Nitisewojo & Hultin, 1986;Stanley & Hultin, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…Such a reaction has been observed in the soil bacteria Bacillus PM6 and Pseudomonas aminovorans [16,17] and in fish muscle where the enzymatic nature has been investigated tentatively [18][19][20]. Contrariwise, it has been suggested that this type of reaction may be catalyzed by nonspecific macromolecules such as hemoglobin, cysteine residues, or even reduced metal ions [21,22].…”
Section: Discussionmentioning
confidence: 97%